Materials and Contact Characterisation IX 2019
DOI: 10.2495/mc190181
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Technique for Testing Osteointegration in Load-Bearing Conditions

Abstract: When a new material for the realization of an implantable device in the bone is being studied, in addition to its chemical-physical-mechanical characterization, tests regarding osteointegration are performed. Usually, researchers evaluate the ability of biomaterials to bind to the bone under load-bearing conditions, through animal experiments in the phase of a preclinical study, provided the respective authorization by the ethics committee. In more detail, plugs made of the material under investigation are pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Therefore, the implementation of a joint approach has permitted relevant steps forward in the understanding of various biomechanical aspects, thus permitting relevant improvements in the clinical sphere, such as in surgical or biomedical procedures [1][2][3][4][5], implants realisation [6][7][8][9][10][11][12] and prosthesis design [13][14][15][16][17]. On the one hand, experimental analysis provides further insights into materials characterisation at different scales [18][19][20][21][22][23][24][25][26], objectifies clinical qualitative outcomes [27][28][29][30][31][32][33][34][35] and lets numerical models be validated [36]. On the other hand, numerical studies allow studying wider test scenarios and inferring physical quantities otherwise tough to figure out because of feasibility and costs reasons [37][38][39][40][41][42][43][44][45]…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the implementation of a joint approach has permitted relevant steps forward in the understanding of various biomechanical aspects, thus permitting relevant improvements in the clinical sphere, such as in surgical or biomedical procedures [1][2][3][4][5], implants realisation [6][7][8][9][10][11][12] and prosthesis design [13][14][15][16][17]. On the one hand, experimental analysis provides further insights into materials characterisation at different scales [18][19][20][21][22][23][24][25][26], objectifies clinical qualitative outcomes [27][28][29][30][31][32][33][34][35] and lets numerical models be validated [36]. On the other hand, numerical studies allow studying wider test scenarios and inferring physical quantities otherwise tough to figure out because of feasibility and costs reasons [37][38][39][40][41][42][43][44][45]…”
Section: Introductionmentioning
confidence: 99%
“…Earlier study showed that the temperature development and its influence on the bone tissue is proportional to the time of exposure to the friction during the drilling procedure [3]. Excessive destruction of the surrounding tissues like crushed bone, necrosis, or bone architecture annihilation influences the possibility of achieving good osteointegration, which is mandatory for dental implant success [4,5]. This bone change can vary according to the drill's design, parameters, and cooling system utilized.…”
Section: Introductionmentioning
confidence: 99%